2019
DOI: 10.1111/jcpt.12809
|View full text |Cite
|
Sign up to set email alerts
|

The impact of implementing an antifungal stewardship with monitoring of 1‐3, β‐D‐glucan values on antifungal consumption and clinical outcomes

Abstract: What is known and objective Implementation of an antifungal stewardship programme is a recognized need. However, there is insufficient information to confirm the impact of antifungal stewardship interventions. Further, few studies have evaluated the clinical effects of an antifungal stewardship intervention using 1‐3, β‐D‐glucan (βDG) testing. The aim of the present study was to evaluate the impact of implementing an antifungal stewardship with monitoring of βDG values on antifungal use and clinical outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…When available, such a rapid test could decrease the time to more targeted therapy, which positively impacts patient outcomes including length of hospitalization and mortality [ 27 29 ]. It could also promote improved antimicrobial stewardship by reducing the amount of time a patient is exposed to inappropriate antimicrobials [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…When available, such a rapid test could decrease the time to more targeted therapy, which positively impacts patient outcomes including length of hospitalization and mortality [ 27 29 ]. It could also promote improved antimicrobial stewardship by reducing the amount of time a patient is exposed to inappropriate antimicrobials [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…A few other studies have shown significant decrease in costs [ 26 , 30 ] and adverse events [ 31 ], without a different impact on survival. However, some of them identified a very small sample size [ 30 , 32 ], and most of them focused on optimizing only high-cost antifungal treatment [ 26 ]. Few studies incorporated therapeutic drug monitoring (TDM) measurement into AFS programs.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers have previously demonstrated a very high negative predictive value of BDG, and clinicians can use a negative result to discontinue empiric antifungal therapy. However, only one published study has shown results on the implementation of BDG within AFS programs [ 32 ]. In the present study, negative BDG results were used to discontinue antifungals in 14 of 43 patients in the intervention phase (32.5%).…”
Section: Discussionmentioning
confidence: 99%
“…The University Medical Center Groningen, the Netherlands No 64% was the adequate posaconazole exposure; in the longitudinal analysis from all the confounders, only dose had a significant effect on posaconazole concentrations Low Kawaguchi et al [ 41 ] Single-centre, observational Candida species Antifungal stewardship programs (AFSPs) 1–3 years Patients who received systemic antifungals at the Osaka City University Hospital (980-bed, tertiary-care teaching hospital) Yes As the appropriate selection of antifungals increases, a decrease in antifungal usage and cost reduction also occurs. This trend leads to improved prognoses of patients with candidemia Low Ito-Takeichi et al [ 42 ] Single-institutional prospective cohort Candida species 1‐3, β - d -glucan (βDG) testing 1–2 days In patients receiving intravenous antifungals at the 614-bed Gifu University Hospital No Parental antifungal use was significantly reduced Low Cavalieri et al [ 46 ] Retrospective Candida species MALDI-TOF mass spectrometry / Vitek 2 1–2 days Hospitalized patients Yes An average 18 h faster microbial ID and antimicrobial susceptibility test results Low Steuber et al [ 18 ] Single-centre, retrospective, observational Candida species T2 Candida Panel (T2CP) 3 years Patients with positive or negative T2CP at a 971-bed community hospital No Antifungal optimization occurred in 54% of patients who had antifungal orders at the time of T2CP test Low Hashemi et al [ 45 ] ...…”
Section: Methodsmentioning
confidence: 99%